Quiet eye as a mechanism for table tennis performance under fatigue and complexity - Vincze, A.; Jurchis, R. (Journal of Motor Behavior, 2022)
QE is the final ocular fixation that precedes critical athletic movements and that enables athletes to gather relevant information and organize their subsequent movement. Although little is known about the factors sustaining performance in table tennis, to date there has been no investigation to assess QE as a contributor to table tennis performance. Furthermore, there is limited research regarding the influence on QE of factors that are known to impact performance, such as task complexity and fatigue. In a within-subjects experimental design, we manipulated fatigue (high vs low) and task complexity (high vs low). Eleven elite table tennis players (mage =14.72 years, mexperience = 7.27 years) underwent each of the four resulting conditions. Athletes made longer QE before hit versus missed shots and QE and performance decreased under fatigue , but we did not detect a significant effect of complexity on QE . This study is one of the first to show that QE sustains performance in a dynamic sport, that is table tennis, and that QE is affected by fatigue.